A103 Who has a bus pass, and is it good for their health? ID: 133. Issue 2 (June 2015) - Webb, Elizabeth; Laverty, Anthony; Millett, Chris
Abstract: Background: The older person's bus pass, introduced in 2006, enables people aged over the state retirement age to travel free on local buses across the UK. Uptake averaged at 75% in 2008-2010 (National Travel Survey data). Existing research suggests that, of those eligible, women, older people, less advantaged people, those who live in London and those who have cars are more likely to hold a bus pass (Coronini-Cronberg et al., 2012). There are also suggestions that older people with bus passes may be more physically active (Coronini-Cronberg et al., 2012) and less likely to be obese (Webb et al., 2011). This paper will investigate who has a bus pass and whether having a bus pass predicts public transport use and adiposity. Methods: Data were drawn from wave 6 of the English Longitudinal Study of Ageing (ELSA), a nationally representative survey of people aged 50 years and older, and their partners, living in England conducted in 2012 and 2013 (N=10, 601). The analytic sample was restricted to those we knew were eligible for a bus pass at ELSA wave 6 interview (N=6870). Holders and non-holders of bus passes were described according to their age, sex, socioeconomic circumstances, car and public transport use, physical activity and adiposity, and multivariable logistic regression was used to determine the predictors of holding a bus pass. Associations between holding a bus pass and public transport use and adiposity were investigated using, respectively, multivariable logistic regression and multivariable linear regression. Models were run separately for men and women where sex interactions were observed. Results: Initial models suggest that i) women, retired people and those in the middle of the wealth distribution are most likely to hold a bus pass ii) people who hold bus passes use public transport more often, and iii) women, but not men, who hold a bus pass have lower levels of adiposity, as measured by BMI and waist circumference, than their peers. Conclusions: These findings suggest that older people who have a bus pass may be more physically active and healthier than those who don't, supporting the growing evidence that there is a public health justification for maintaining the older person's bus pass.